A Marogan Tour and Travel Web Profile Development Strategy Using Business Model Canvas Analysis - Abelia Zahrah Febrianty; Yulia Pebrianti; Tsurayya Syarif Zain (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to develop the web profile of Marogan Tour and Travel through the implementation of strategies analyzed using the Business Model Canvas approach. Method: The methods used in this research include literature review, observation, interviews, and documentation. The analysis is based on nine key elements of the Business Model Canvas: customer segments, value propositions, distribution channels, customer relationships, key resources, key activities, key partners, cost structure, and revenue streams. Result: The web development results include updates to the homepage, about us, services, gallery, and contact pages, with features that support customer needs and reflect Business Model Canvas elements. For example, easy access to information is achieved through a responsive and informative display, and communication is enhanced through interactive features like the WhatsApp button. Contribution: This research expands the existing study on the use of the Business Model Canvas in web profile development by demonstrating how elements of the Business Model Canvas can be applied to strengthen a company's digital strategy. Practically, this research provides guidance for tourism businesses in designing more effective, informative, and interactive web profiles, thereby improving service, communication, and potential customer conversion.